Konstruksi Relasi Dakwah di Pondok Pesantren Sindangsari Al-Jawami - Muhamad Aliman (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2018)
The purpose of this research is to develop, understand and analyze Kyai with students, especially in the life of the boarding school